The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.3354/cr025043
|View full text |Cite
|
Sign up to set email alerts
|

Examining the ENSO-typhoon hypothesis

Abstract: Modern typhoon data and historical documents from Guangdong Province, southern China, are analyzed and found to support the El Niño-Southern Oscillation (ENSO)-typhoon hypothesis. The hypothesis states that tropical cyclone formation during an El Niño event shifts eastward, with typhoons tending to recurve north, staying away from China. From the comprehensive but short modern record, typhoon tracks are grouped into 3 distinct clusters based on geographic position at maximum and terminal typhoon intensities. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
153
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(161 citation statements)
references
References 43 publications
(52 reference statements)
7
153
1
Order By: Relevance
“…Linking the Japan historical chronologies to chronologies developed for China (Chan and Shi, 2000;Liu et al, 2001;Elsner and Liu, 2003;Fogarty et al, 2006), the Philippines (Ribera et al, 2005;García-Herrera et al, 2007;Ribera et al, 2008) and possibly Korea and Taiwan will make it possible to investigate longer-term patterns of typhoon formation and behaviour throughout the WNP. Combining data from many countries in the region will also make it possible to map historical typhoon tracks for the entire WNP to better understand the variability of typhoon behaviours over longer time periods under climatic conditions differing from those of the late twentieth and early twenty-first centuries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Linking the Japan historical chronologies to chronologies developed for China (Chan and Shi, 2000;Liu et al, 2001;Elsner and Liu, 2003;Fogarty et al, 2006), the Philippines (Ribera et al, 2005;García-Herrera et al, 2007;Ribera et al, 2008) and possibly Korea and Taiwan will make it possible to investigate longer-term patterns of typhoon formation and behaviour throughout the WNP. Combining data from many countries in the region will also make it possible to map historical typhoon tracks for the entire WNP to better understand the variability of typhoon behaviours over longer time periods under climatic conditions differing from those of the late twentieth and early twenty-first centuries.…”
Section: Discussionmentioning
confidence: 99%
“…Regionally, Liu et al (2001) found that 1850-1880 was a period of frequent typhoon strikes on Guangdong in southern China while the 1880s had a frequency near the lower end of decadal means in the record (1600-1900). Based on the inverse relationship between typhoons taking a straight track towards southern China and those recurving towards Japan (Elsner and Liu, 2003), this indicates that the 1880s would have been a decade with more frequent typhoons affecting Japan. A reconstruction of northwest Pacific typhoons from Philippine Jesuit records (García-Herrera et al, 2007) suggests that an increased number of typhoons making landfall in the Philippines in the 1880s marked the end of a period of lower annual frequencies of typhoons during the second half of the nineteenth century.…”
Section: Reconstructing Typhoonsmentioning
confidence: 99%
See 2 more Smart Citations
“…[Fujii et al, 2002;Kohno et al, 2010]). Because typhoons which reach Japan commonly take recurving paths toward northeast and are attenuated by the move into the belt of westerlies, Hokkaido, the northernmost island of Japan, is usually away from the paths of strong typhoons ( [Elsner and Liu, 2003]). As a consequence, Hokkaido had never experienced any recorded storm surge disaster, and hardly any measure to reduce tidal flood impacts had been taken there.…”
Section: Introductionmentioning
confidence: 99%